Electron microscopy of simian virus 40 DNA configuration under denaturation conditions. - Mayer, F (1975)
After isolation, the DNA of simian virus 40 appeared as a negative supertwist (form I) or as an open circle with at least one single-strand scission (form II). Under the denaturation conditions usually applied, such as heating in the presence of formaldehyde or application of alkali, form I molecules could appear as "relaxed" circles without single-strand scissions (form I') containing denatured sites not visible under the electron microscope. Form II molecules, under these denaturation conditions, showed partial or complete strand separations allowing the construction of denaturation maps. By using a modified denaturation procedure, i.e., heating of isolated SV40 DNA in the presence of dimethyl sulfoxide and formaldehyde followed by keeping the DNA in this denaturation solution at room temperature for periods up to 3 weeks, partially denatured relaxed circles without single-strand scissions were produced (form I'D) in addition to completely denatured form II molecules. The absence of single-strand scissions in form I'D molecules was demonstrated by a second heat treatment, which did not change the configuration of this molecular form. Form I'D molecules, in contrast to form I', contained denatured sites clearly discerible under the electron microscope. This combined application of two subsequent denaturation steps (denaturation by heating followed by denaturation at room temperature and neutral pH) showed that the molecular configuration I'D originated in two steps. The heating procedure produced molecules not distinquishable by electron microscopy from form I. In contrast to form I, these molecules were assumed to possess "preformed" denaturation sites (form I). Further treatment of form I molecules with denaturation solution at room temperature finally transformed them into convalently closed, relaxed, partially denatured circles exhibiting strand separations easily measurable on electron micrographs (form I'D). Denaturation maps of form I'D molecules were constructed by computer and compared with denaturation maps derived from partially denatured form II molecules. From these denaturation maps it can be concluded that the melting of base pairs occurring during the transition of simian virus 40 DNA form I into form I'D also preferentially happened at sites rich in the bases adenosine and thymine.